Role of aliasing and interacting factors in the enhanced production of dehalogenase from Yarrowia lipolytica for degradation of brominated compounds - Vatsal, Aakanksha; Potdar, Chirag; Smita S. Zinjarde; Kumar, V. Ravi; Kulkarni, Bhasker D.; RaviKumar, Ameeta (Journal of Industrial and Engineering Chemistry, 2016)
Use of persistent organobromines for industrial applications has led to their accumulation in environment. Yarrowia lipolytica NCIM 3589, a tropical marine yeast, degrades and detoxifies bromocompounds by an initial hydrolytic step. By optimizing culture conditions with 1-bromodecane as reference compound, the dehalogenase involved was remarkably enhanced 13-fold (384.13 U/ml) by a hybrid statistical Plackett-Burman and Box-Behnken design of experiments. Studies bring out in a novel way the role of aliasing and other masked interactions in growth media factors. Importantly, the enzyme acted on C3-C16 bromoalkanes and bromoaromatics, thereby generalizing the 'green chemistry' applicability of optimized media formulation for biotechnological applications. (C) 2016 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.